Determination of Ethyl Xanthate in Aqueous Solution by High Performance Liquid Chromatography–Inductively Coupled Plasma–Tandem Mass Spectrometry and Spectrophotometry. (2nd June 2022) - Suvela, Ronja; Niemelä, Matti; Perämäki, Paavo
Abstract: Xanthates are commonly used collectors in flotation processes but are highly toxic to the aquatic environment. However, there are few methods for reliable determination of low xanthate concentrations in water samples. In this work, a sensitive, selective, and fast method is presented for the determination of potassium ethyl xanthate (KEX). KEX was determined by high-performance liquid chromatography–inductively coupled plasma–mass spectrometry (HPLC-ICP-MS/MS) directly and as diethyl dixanthogen [(EX)2 ] after oxidation with triiodide. The HPLC method was optimized for (EX)2 and the separated compounds were detected by ICP-MS/MS. The ICP-MS/MS was used in mass-shift mode using O2 as the cell gas and S + was measured as SO + to reduce spectral interferences. Detection limits of 88 µg L −1 for KEX and 20 µg L −1 for (EX)2 calculated from the peak area were obtained using mass-shift 32 S + → 32 S 16 O + . No significant matrix effects were present when spiking experiments of (EX)2 were done to a sample collected from the tailings of a flotation process. The developed method demonstrates the potential of the HPLC-ICP-MS/MS for the determination of ethyl xanthate. This method may be extended to analyzing other xanthates and similarly structured sulfur containing collectors.